Does God Answer Only Trivial Prayers? - Paulien, Jon (Revista Estrategias para el Cumplimiento de la Misión, 2015)
The Bible tells us that our God is a God of love (John 3:16; 1 John 4:8, etc.). He is way more willing to give good gifts to His “children” than even the most loving earthly father is (Matt 7:7-11). To put it in other words, God enjoys showering His beloved ones with little gifts. Just to say “I love you.” And I believe He loves to do this in some of the most personal and practical ways imaginable. Perhaps you’ve just lost hope of finding a parking spot in time to meet a critical appointment. You send up a desperate prayer and suddenly a space appears. A wor- ried mother wonders where her boy is and sends up a quick prayer. Just then the phone rings and she discovers all is well. Or you survive a har- rowing experience and discover later that several friends felt impressed to pray for you at exactly that time. Millions of believers around the world have experiences just like this every day. It is reasonable to sug- gest from this that God is real and that He loves to make His presence known to those who are open to it.